Why Feuerstein Remains Important in the 21st Century: to Improve Thinking Skills and Inclusive Education - Reflections at the Occasion of the 100th birthday of Reuven Feuerstein - Jo Lebeer (Pensa MultiMedia, 2022)
Although Feuerstein's theory of Structural Cognitive Modifiability and Mediated Learning Experience and its applied systems Learning Propensity Assessment and Instrumental Enrichment are already 70 years old, and do not have modern 21st century looks, Feuerstein's approach remains highly relevant for the needs of teachers and learners in our times: inclusive education, the need to attend to a diversity of pupils at school, increasing numbers of children with learning or behaviour difficulties, ADHD or otherwise, the increasing digitalisation of society, the loss of social cohesion. These are hard challenges for teachers. This article starts making a critical cultural-historical reflection on the so-called "21st century cognitive challenges" and of characteristics of the Feuerstein programme. Then three case studies are presented were LPAD followed by a cognitive-mediational intervention made a turning point in their educational trajectory: a child and an adolescent with Down syndrome, and a recent African immigrant. The case studies underpin a further reflection why the Feuerstein approach offers a suitable answer to the discussed challenges.